SURVEY THE RELATIONSHIP BETWEEN FECAL OCCULT BLOOD TEST WITH COLORECTAL POLYPS IN 510 WORKERS AT TAN CANG MEDICAL CENTER - Pham Thi Thuy; Phan Ha Phu; Cao Thi La (Tạp chí Y học Quân sự, 2023)
Pham Thi Thuy Md., Msc. Phan Ha Phu Md. Cao Thi La Md. Tan Cang Medical Center